Ambyrne wind, amberlice and byre in the DOE Online. (26th April 2019) - Korhammer, Michael
Abstract: This article, which builds on an older publication of the author's, argues on the basis of nautical, linguistic and logical evidence that some widely accepted opinions on the meaning of the Old English words in the title cannot be upheld any further.